The role of serum angiopoietin-2 levels in progression and prognosis of lung cancer: A meta-analysis - Xu, Yuyang (Medicine (Baltimore), 2017)
BACKGROUND: Angiogenesis is an essential process in the development and progression of malignant tumors including lung cancer, in which angiopoietin-2 (Ang-2) plays an important role. The objective of this study was to assess the prognostic value of serum Ang-2 levels in patients with lung cancer. METHODS: A comprehensive systematic electronic search was performed in the Pubmed, Embase, Web of Science, china national knowledge infrastructure, and VIP databases update to October, 2016 (qikan.cqvip.com). Literatures examining the relevance of serum Ang-2 levels to progression and prognosis of lung cancer were eligible for our study. Standardized mean differences (SMD) with 95% confidence interval (95% CI) and a P value were applied to compare continuous variables, and hazard ratio (HR) with 95% CI as well as P value were applied for prognostic role. RESULTS: Twenty studies with 1911 patients met the eligibility criteria. Among them, 7 studies with 575 patients with lung cancer assessed the association between expression of serum Ang-2 and prognosis. According to our results, higher levels of serum Ang-2 were associated with the later stage of tumor. Serum Ang-2 levels were significantly lower in stage I than in stage II (SMD: −0.51; 95% CI: −0.75 to −0.27; P < .001), in stage II than in stage III (SMD: −0.52; 95% CI: −0.80 to −0.24; P < .001), in stage III than in stage IV (SMD: −0.58; 95% CI: −0.93 to −0.23; P = .001). In addition, serum Ang-2 levels were higher in patients with lymph node metastasis (SMD: 1.06; 95% CI, 0.57–1.56; P < .001). Meanwhile, patients with lung cancer with higher levels of serum Ang-2 were associated with a significant poorer prognosis when compared to those with lower serum Ang-2 levels (HR: 1.64; 95% CI: 1.20–2.25; P = .002), and this role was further detected when stratified by ethnicity and histological type. CONCLUSIONS: This systematic review and meta-analysis suggested that serum Ang-2 levels might be a potential predictor for staging, and were associated with prognosis of lung cancer.